The Influence of Empathy and Self-Control on Verbal Bullying Behavior in Elementary School Children - Bungge, Tirsa Raintowe; Hasan, Hasan; Nurwahyuni, Nurwahyuni; Riyadi, Nur Eka Wahyuningsih; Rasido, Ikhlas (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2026)
Verbal bullying is a form of aggression that often occurs in school environments, influenced by psychological factors such as low empathy and self-control. This study aims to determine the effect of empathy and self-control on verbal bullying behavior in elementary school children. This study uses a quantitative causal associative research design with a population of 352 students in grades IV to VI at four elementary schools in the East Palu region. The sample consisted of 187 respondents. Data collection was conducted using a questionnaire containing scales for empathy, self-control, and verbal bullying behavior. The data were analyzed using descriptive analysis and multiple linear regression analysis. The results showed that (1) empathy had a positive and significant effect on verbal bullying behavior, (2) self-control had a positive and significant effect on verbal bullying behavior, and (3) simultaneously, empathy and self-control had a significant effect on verbal bullying behavior. Based on the hypothesis testing results, all hypotheses in this study were accepted. Thus, it can be concluded that the lower the empathy and self-control, the higher the tendency for verbal bullying behavior in elementary school children. This study confirms that strengthening empathy and self-control is important as an effort to prevent verbal bullying behavior in elementary schools.